2006
DOI: 10.1176/appi.ps.57.6.772
|View full text |Cite
|
Sign up to set email alerts
|

Economic Grand Rounds: Variation in Staffing and Activities in Psychiatric Inpatient Units

Abstract: In 1999 the Balanced Budget Refinement Act mandated the development of a per diem prospective payment for all psychiatric inpatients. To assist Medicare in developing a per diem patient-based payment system, this study surveyed a representative sample of psychiatric inpatient units in 40 facilities for one week in 2001 through 2003 to determine how units are staffed and how staff members spend their time caring for patients. On general adult units, psychiatric staff averaged ten hours per patient per 24-hour d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Precision of the database search was comparatively low. Eight publications were eventually included from 15 536 unique records identified in the database search (Autio, 1987; Fries et al 1990, 1993; Cromwell et al 2004, 2005 b ; Iglesias & Alonso Villa, 2005; Cromwell & Maier, 2006; Drozd et al 2006). Eight of 17 publications were grey literatures (Yamauchi, 1997 a , b ; Buckingham et al 1998 a , b ; Hirdes et al 2002; Gaines et al 2003; Cromwell et al 2005 a ; Daniel, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision of the database search was comparatively low. Eight publications were eventually included from 15 536 unique records identified in the database search (Autio, 1987; Fries et al 1990, 1993; Cromwell et al 2004, 2005 b ; Iglesias & Alonso Villa, 2005; Cromwell & Maier, 2006; Drozd et al 2006). Eight of 17 publications were grey literatures (Yamauchi, 1997 a , b ; Buckingham et al 1998 a , b ; Hirdes et al 2002; Gaines et al 2003; Cromwell et al 2005 a ; Daniel, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were conducted in multiple sites with large sample sizes (Group A) and two studies at a single site with smaller sample sizes (Group B). All studies in Group A were reported in multiple publications (Study 1: Cromwell et al 2004, 2005 a , b ; Cromwell & Maier, 2006; Drozd et al 2006; Study 2: Gaines et al 2003; Eagar et al 2004; Study 3: Hirdes et al 2002; Daniel, 2008; Study 4: Buckingham et al 1998 a , b ; Study 5: Yamauchi, 1997 a , b ; Study 6: Fries et al 1990, 1993). A total of 15 613 patient episodes were included with a range of 42–6554.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a limited number of medical psychiatric beds are available to care for the higher rate of comorbid medical conditions in this population. Estimates report that more than 20% of geriatric patients have mental disorders, and as the U.S. population continues to age, this number is expected to double over the next 30 years 19. Cromwell and Maier19 demonstrated that these medical psychiatric units and geriatric psychiatric units require the most staff hours per patient per day compared with general adult units, psychiatric intensive care units, and dual psychiatric and substance-abuse units 20.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates report that more than 20% of geriatric patients have mental disorders, and as the U.S. population continues to age, this number is expected to double over the next 30 years 19. Cromwell and Maier19 demonstrated that these medical psychiatric units and geriatric psychiatric units require the most staff hours per patient per day compared with general adult units, psychiatric intensive care units, and dual psychiatric and substance-abuse units 20. The burgeoning geriatric population and the increased requisite psychiatric resources likely will pose challenges for inpatient placement and may continue to increase the transfer rate for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, available evidence suggests that patients on psychiatric units have multiple and complex physical and mental health problems that require the attention of an RN (Druss & Reisinger Walker, 2011; Kronick, Bella, & Gilmer, 2009; Safford, Allison, & Kiefe, 2007; Valderas, Starfield, Sibbald, Salisbury, & Roland, 2009). A main determinant of patient outcomes from psychiatric hospitalizations is the type of patient who is admitted and the type of psychiatric facility that delivers the care (Cromwell & Maier, 2006). In 2002, 1.6 million Americans aged 18 years and older were hospitalized for a psychiatric condition, for a total of 2.2 million psychiatric admissions (OAS, 2005; National Center for Health Statistics, 2006).…”
Section: Discussionmentioning
confidence: 99%